2003
DOI: 10.1038/sj.leu.2402963
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of BCR/ABL gene rearrangements by interphase fluorescence in situ hybridization (FISH) in BCR/ABL+ leukemias: incidence and underlying genetic abnormalities

Abstract: Interphase fluorescence in situ hybridization (iFISH) is increasingly used for the identification of BCR/ABL gene rearrangements in chronic myeloid leukemia (CML) and acute lymphoblastic leukemia (ALL). In the present study, we have explored the incidence of both typical and atypical iFISH patterns of BCR/ABL gene rearrangements in a series of 168 consecutive BCR/ABL + patients -135 CML, 31 precursor B-ALL and two acute myeloblastic leukemia (AML) cases -and established their underlying genetic alterations thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 26 publications
5
44
1
Order By: Relevance
“…In contrast, two patients (1%) had a normal karyotype with no Ph chromosome being detected; the BCR/ABL gene rearrangements observed in both cases were due to a cryptic insertion of BCR in 9q34, as confirmed by metaphase FISH. These findings, together with those of Wan et al, 1 would support the notion that, in patients in whom a CML is suspected to show an iFISH pattern consistent with an apparent 9q À and a Ph-negative karyotype, interphase and metaphase FISH investigation of atypical BCR/ABL gene rearrangements should be searched to confirm the presence of cryptic BCR insertion in 9q34. As already mentioned in our previous work, 2 in none of our two cases, neither in the one reported by Wan et al, 1 nuclei carrying a typical MBCR/ABL gene translocation were simultaneously found.…”
Section: To the Editorsupporting
confidence: 56%
See 1 more Smart Citation
“…In contrast, two patients (1%) had a normal karyotype with no Ph chromosome being detected; the BCR/ABL gene rearrangements observed in both cases were due to a cryptic insertion of BCR in 9q34, as confirmed by metaphase FISH. These findings, together with those of Wan et al, 1 would support the notion that, in patients in whom a CML is suspected to show an iFISH pattern consistent with an apparent 9q À and a Ph-negative karyotype, interphase and metaphase FISH investigation of atypical BCR/ABL gene rearrangements should be searched to confirm the presence of cryptic BCR insertion in 9q34. As already mentioned in our previous work, 2 in none of our two cases, neither in the one reported by Wan et al, 1 nuclei carrying a typical MBCR/ABL gene translocation were simultaneously found.…”
Section: To the Editorsupporting
confidence: 56%
“…2 Despite the observation of a normal karyotype, the presence of the BCR/ABL gene fusion on chromosome 9 was confirmed by FISH on metaphase chromosomes, using the two mentioned probes plus a third BCR/ABL dual-color signal fusion (S-FISH) probe (Vysis). 1 In an updated series of 182 CML patients, we have found 15 cases (8%) showing similar patterns with the ES probe: one red, one green and one fused red/green signal (1R1G1F). This is in line with the previously published incidence of this pattern.…”
Section: To the Editormentioning
confidence: 99%
“…A number of cryptic insertions of either BCR into ABL at 9q34, as reviewed by Primo et al, 24 or rarely ABL into BCR at 22q11, 25 have been reported in CML, with the insertions confirmed by dual fusion FISH. 7,18,[25][26][27][28] An insertion is sometimes seen as the end point of a series of events. Thus, in our case, either the der(9) chromosome which provided ABL sequences to chromosome 22 could have been lost, with subsequent duplication of the normal copy of chromosome 9, or else there could have been a partial duplication of ABL sequences on the der(9), which preceded their insertion into chromosome 22.…”
Section: Discussionmentioning
confidence: 99%
“…The designs of the SF and the ES probes allow detection of breakpoints involving the m-bcr of the BCR gene as well as the BCR/ABL fusion. 17,18 The interphase FISH patterns expected with each probe are shown in Table 1. For those cases with standard and nonstandard signal patterns observed in interphase, the number and relative size of the signals were confirmed, where possible, on representative metaphase cells from the same samples.…”
Section: Fishmentioning
confidence: 99%
“…This is in line with the previously published incidence of this pattern. 2,3 In most of these 15 cases (n ¼ 13; 7%), the presence of an extensive del(9q) was confirmed by metaphase analyses with both the ES and the D-FISH probes; all of them showed a typical Ph chromosome on conventional cytogenetics. In contrast, two patients (1%) had a normal karyotype with no Ph chromosome being detected; the BCR/ABL gene rearrangements observed in both cases were due to a cryptic insertion of BCR in 9q34, as confirmed by metaphase FISH.…”
mentioning
confidence: 99%